2009
DOI: 10.1002/jat.1483
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of polychlorinated biphenyl hydroquinone metabolites in rat hepatocytes

Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants that exhibit various toxic effects in animals and exposed human populations. The molecular mechanisms of PCB toxicity have been attributed to the toxicological properties of its metabolites, such as hydroquinones, formed by cytochrome-P-450 oxidation. The effects of PCB hydroquinone metabolites towards freshly isolated rat hepatocytes were investigated. Hydroquinones can be oxidized to semiquinones and/or quinone metabolites. These metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The results of this study showed that PCBs exposure caused a significant decrease in the testicular T‐SHs whereas it increased the ROS and TBARS levels, thus evidencing a state of oxidative stress. The reduction in the intracellular T‐SHs level in PCBs‐treated rats could indicate its overutilisation and/or oxidation following PCBs exposure (Chan et al ., ; Aly, ). Pro‐oxidative alterations in the intracellular thiol status are well known to adversely affect cellular processes (Fourquet et al ., ; Kumar et al ., ; Toledano et al ., ; Adedara & Farombi, ).…”
Section: Discussionmentioning
confidence: 97%
“…The results of this study showed that PCBs exposure caused a significant decrease in the testicular T‐SHs whereas it increased the ROS and TBARS levels, thus evidencing a state of oxidative stress. The reduction in the intracellular T‐SHs level in PCBs‐treated rats could indicate its overutilisation and/or oxidation following PCBs exposure (Chan et al ., ; Aly, ). Pro‐oxidative alterations in the intracellular thiol status are well known to adversely affect cellular processes (Fourquet et al ., ; Kumar et al ., ; Toledano et al ., ; Adedara & Farombi, ).…”
Section: Discussionmentioning
confidence: 97%
“…SOD, CAT, GST and GPx, were measured with assay kits. 39 GPx activity was measured by following the absorbance at 412 nm on the basis of the oxidation of NADPH with H 2 O 2 . CAT activity was determined by measuring the H 2 O 2 decomposition (absorbance at 240 nm).…”
Section: Determination Of Antioxidant Enzyme Activitiesmentioning
confidence: 99%
“…38 GST activity was measured on the basis of the conjugation reaction of 1-chloro-2,4-dinitrobenzene with GSH whose product has maximum absorbance at 412 nm. 39 GPx activity was measured by following the absorbance at 412 nm on the basis of the oxidation of NADPH with H 2 O 2 . 40…”
Section: Determination Of Antioxidant Enzyme Activitiesmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) are persistent organic pollutants found in the environment and in tissue samples (Chan et al, 2010;Tilson and Kodavanti, 1997;Tilson et al, 1990). In addition, their chemical and physical stability inhibits their degradation, leading to their ubiquitous presence in the biosphere (Bushnell et al, 2002); their lipophilicity has facilitated the bioaccumulation of these compounds and their metabolites in the food chain.…”
Section: Introductionmentioning
confidence: 99%